2021
DOI: 10.5958/2231-5713.2021.00007.6
|View full text |Cite
|
Sign up to set email alerts
|

Design and optimization of clotrimazole emulgel by using various polymers

Abstract: Emulgel is one of the recent technologies in Novel Drug Delivery system (NDDS) used for dual controlled release of emulsion and gel for topical use. The stability of emulsion is increased, when it is incorporated into gel. Clotrimazole is a broad spectrum anti -fungal agent, also a hydrophobic drug. It is difficult to formulate as topical delivery. So emulgel is one of the best approaches to incorporate hydrophobic drugs. The purpose of the present study was to develop and optimized the Clotrimazole emulgel us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…0.5M silver nitrate solution was prepared in distilled water on other hand green tea extract was prepared by adding the tea bag in 100 ml boiling water. In a separate beaker, the required amount of silver nitrate solution was added and then 1 ml of green tea extract was also added, kept the solution for 5 min [11]. Silver nitrate solution started to change the colour from white to brown this indicated that silver nitrate has been reduced by green tea antioxidant and it has converted into nanoparticles.…”
Section: Synthesis Of Silver Nanoparticlesmentioning
confidence: 99%
“…0.5M silver nitrate solution was prepared in distilled water on other hand green tea extract was prepared by adding the tea bag in 100 ml boiling water. In a separate beaker, the required amount of silver nitrate solution was added and then 1 ml of green tea extract was also added, kept the solution for 5 min [11]. Silver nitrate solution started to change the colour from white to brown this indicated that silver nitrate has been reduced by green tea antioxidant and it has converted into nanoparticles.…”
Section: Synthesis Of Silver Nanoparticlesmentioning
confidence: 99%